Bone Adherence of Immediate Loaded Dental Implants- A Clinico- Radiographic Study - Irshad Ahmad; Masroor Khurshied Shah; Saniya Farooq (Asian Journal of Medical Research, 2023)
Background: The purpose of this study was to evaluate the the bone adherence of immediate loaded dental implants, clinically and radiographically. Subjects and Methods: 20 implants in the form of single crowns or 2- 4 unit bridges were placed in 10 patients. The implants were loaded  immediately. The patients were followed up at 2/3 months, 6 months, 12 months, 24 months of post implant insertion. Post-operative evaluation included: Implant mobility;; Peri-implant Radiolucency; & Bone loss. Results: All  the clinical parameters were comparable & statistically non- significant. the overall success rate for these immediate loaded dental implants was recorded as 100%. Conclusion: Within the limitations of this study, immediate loading of dental implants is a suitable treatment option in both mandible & maxilla.